Prevalence of vaccine hesitancy and its associated factors in an urban area of West Bengal, India - Sikder, Rajib; Mukherjee, Dipankar; Pattanayak, Ujjwal; Majumdar, Kunal Kanti; Kundu, Subha Sankha; Dey, Rituraj; Joardar, Gautam Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Vaccine hesitancy is delay in acceptance or refusal of vaccines despite availability of vaccine services. This study was conducted to find out the prevalence and factors associated and contributing to vaccine hesitancy for childhood vaccinations in Rajpur-Sonarpur municipalty of south 24 parganas, India. Methods: A cross‑sectional study was done among 352 children aged 0-59 months. Hesitancy to all childhood vaccination including the birth doses were observed. By simple random sampling ward no 8 was selected among the 37 wards of Rajpur-Sonarpur municipalty. All the vaccination center of ward no 8 on various vaccination days were covered from July 2019- December 2019. Data were collected at these vaccination centers by interviewing parents /associates of the children. Validated version of vaccine hesitancy survey questionnaire by the World Health Organization was used. Results: Vaccine hesitancy was present among 103 (29%) parents/relatives /associates of children. Delay was more common for measles and the booster doses of other vaccines. Reluctance to vaccinate was the most common reason (26.2%) for vaccine hesitancy. About 15(15.4%) parents reported to be unaware or confused of when to vaccinate their children. Improper counselling by health care givers, illness or irritability of the child were other causes. Conclusions: To avoid delay in vaccination weekly vaccination days were recommended. Community level campaigning and home visit of those eligible children to generate awareness about vaccination and to avoid reluctance in parents/associates of children were suggested.